Correlation of Quantitative Diffusion Tensor Tractography with Clinical Grades of Subacute Sclerosing Panencephalitis - Trivedi, R.; Anuradha, H.; Agarwal, A.; Rathore, R.K.S.; Prasad, K.N.; Tripathi, R.P.; Gupta, R.K. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: SSPE is a persistent infection of the central nervous system caused by the measles virus. The correlation between the clinical staging and conventional MR imaging is usually poor. The purpose of this study was to determine whether tract-specific DTI measures in the major white mater tracts correlate with clinical grades as defined by the Jabbour classification for SSPE. MATERIALS AND METHODS: Quantitative DTT was performed on 20 patients with SSPE (mean age, 9 years) and 14 age- and sex-matched controls. All patients were graded on the basis of the Jabbour classification into grade II (n = 9), grade III (n = 6), and grade IV (n = 5) SSPE. The major white matter tracts quantified included the CC, SLF, ILF, CST, CNG, SCP, MCP, ICP, ATR, STR, and PTR. RESULTS: Although a successive decrease in mean FA values was observed in all the fiber tracts except for the SCP and ICP, moving from controls to grade IV, a significant inverse correlation between clinical grade and mean FA values was observed only in the splenium (r= −0.908, P < .001), CST (r = −0.663, P = .013), SLF (r = −0.533, P = .050), ILF (r = −0.776, P = .001), STR (r = −0.538, P = .047), and PTR (r = −0.686, P = .035) fibers. No significant correlation of mean MD values from these white matter tracts was observed with clinical grades of the disease. CONCLUSIONS: We conclude that the grade of encephalopathy correlates inversely with the tract-specific mean FA values. This information may be valuable in studying the disease progression with time and in assessing the therapeutic response in the future. ATRanterior thalamic radiationsCCcorpus callosumCC1rostrumCC2genuCC3rostral bodyCC4anterior midbodyCC5posterior midbodyCC6isthmusCC7spleniumCNGcingulumCSTcorticospinal tractsDTIdiffusion tensor imagingDTTdiffusion tensor tractographyEEGelectroencephalographyFAfractional anisotropyFLAIRfluid-attenuated inversion recoveryICPinferior cerebellar peduncleILFinferior longitudinal fasciculusMCPmiddle cerebellar peduncleMDmean diffusivityPP valuePTRposterior thalamic radiationsRcorrelationSCPsuperior cerebellar peduncleSFMstable fiber massSLFsuperior longitudinal fasciculusSSPEsubacute sclerosing panencephalitisSTRsuperior thalamic radiations